ANALYSIS OF HEAVY METAL CONTENT IN SALT (CASE STUDY OF SALT FIELD, LOSARANG DISTRICT, INDRAMAYU REGENCY) - Mutiara - Salsabiela (Journal of Green Science and Technology, 2021)
Salt is a staple food needed for human life, especially for industrial and household consumption. The raw material for making the salt comes from sea water which is very susceptible to contamination by contaminants in the form of heavy metals. The presence of heavy metals in salt will be harmful to human health when consumed. The study was conducted to determine the quality of salt free from heavy metal contamination and suitable for consumption. in Losarang District, Indramayu Regency. This research was conducted by descriptive method. Data collection techniques were carried out through observation and interviews. The samples tested were salt produced with TUF technology and Geoisolator. The sampling technique refers to SNI 19-0428-1998 regarding the instructions for taking solid samples where the sample is taken using a spear and inserted into a plastic clip that has been labeled with the name and code. The parameters tested were heavy metals consisting of Lead (Pb), Cadmium (Cd), Mercury (Hg) and Arsenic (As). The method of testing the content of heavy metals in salt in this study used the AAS (Atomic Absorption Spectrophotometer) method which was carried out in the